No Evidence for Effects of Ecological and Behavioral Factors on Eye Size Evolution in Anurans - Chen, Chuan; Jiang, Ying; Jin, Long; Liao, Wen Bo (Frontiers in Ecology and Evolution, 2021)
Eye size varies markedly among taxonomic levels, and this variation is often related to the patterns shaped by phylogeny and ecological and behavioral factors. The selective pressures underlying eye size evolution are especially studied in fishes, anurans, birds, and mammals. However, selective pressures underlying the eye size evolution in anurans have inconsistent scaling rules. Here, we investigated the links between eye size and both ecological (e.g., light availability and habitat type) and behavioral factors (e.g., activity time, foraging mobility, defensive strategy, and mating system) among 252 species of anurans by using Markov Chain Monte Carlo generalized linear mixed models. Results show that anuran eye size scales hypo-allemetrically with body size. However, eye size was not significantly influenced by ecological and behavioral factors, including habitat type, activity time, light availability, foraging mobility, defensive strategy, and mating system. Therefore, neither ecology nor behavior plays a key role in promoting eye size evolution in frogs.